Myeloma Cells Down‐Regulate Adiponectin in Bone Marrow Adipocytes Via TNF‐Alpha. (16th January 2020) - Morris, Emma V; Suchacki, Karla J; Hocking, Joseph; Cartwright, Rachel; Sowman, Aneka; Gamez, Beatriz; Lea, Ryan; Drake, Matthew T; Cawthorn, William P; Edwards, Claire M
ABSTRACT: Multiple myeloma is caused by abnormal plasma cells that accumulate in the bone marrow and interact with resident cells of the bone microenvironment to drive disease progression and development of an osteolytic bone disease. Bone marrow adipocytes (BMAds) are emerging as having important endocrine functions that can support myeloma cell growth and survival. However, how BMAds respond to infiltrating tumor cells remains poorly understood. Using the C57BL/KaLwRij murine model of myeloma, bone marrow adiposity was found to be increased in early stage myeloma with BMAds localizing along the tumor‐bone interface at later stages of disease. Myeloma cells were found to uptake BMAd‐derived lipids in vitro and in vivo, although lipid uptake was not associated with the ability of BMAds to promote myeloma cell growth and survival. However, BMAd‐derived factors were found to increase myeloma cell migration, viability, and the evasion of apoptosis. BMAds are a major source of adiponectin, which is known to be myeloma‐suppressive. Myeloma cells were found to downregulate adiponectin specifically in a model of BMAds but not in white adipocytes. The ability of myeloma cells to downregulate adiponectin was dependent at least in part on TNF‐α. Collectively our data support the link between increased bone marrow adiposity and myeloma progression. By demonstrating how TNF‐α downregulates BMAd‐derived adiponectin, we reveal a new mechanism by which myeloma cells alter the bone microenvironment to support disease progression. © 2019 The Authors. Journal of Bone and Mineral Research published by American Society for Bone and Mineral Research.